Efficacy and safety of oral ketamine for the relief of intractable chronic pain: A retrospective 5‐year study of 51 patients. (10th November 2014) - Marchetti, F.; Coutaux, A.; Bellanger, A.; Magneux, C.; Bourgeois, P.; Mion, G.
Abstract Background This work summarizes the efficiency, failures and adverse effects of oral administration of ketamine at home for intractable pain. Methods This 5‐year retrospective study involved testing ketamine by intravenous in‐hospital administration, then a conversion to an oral route, or oral treatment directly administered at home. The daily intravenous dose was increased by steps of 0.5 mg/kg to attain an effective daily dose of 1.5–3.0 mg/kg. Pain was evaluated on a numeric scale from 0 to 10, and evidence of adverse effects was collected every day. The effective daily dose was delivered orally (three to four intakes). If effective, ketamine was continued for 3 months. Short infusions or direct oral treatment began with a 0.5‐mg/kg dose, then the daily ketamine dose was increased in 15‐ to 20‐mg increments. Results Among 55 cases (51 patients, neuropathic pain 60%), the mean effective oral dose was 2 mg/kg. Ketamine was effective in 24 patients (44%, mean pain reduction 67 ± 17%), partially effective in 20% (mean pain reduction 30 ± 11%), with a mean opioid sparing of 63 ± 32%, and failure in 22%. Half of the patients experienced adverse effects, but only eight had to stop treatment. For patients with opioid therapy, failure of ketamine was less frequent (7% vs. 36%; p < 0.02), with fewer adverse effects (33% vs. 68%; p < 0.01). Conclusions Pain was reduced or abolished in two‐thirds of patients under ketamine therapy; ketamine was effective for patients taking opioids and resulted in few adverse effects.